Penguatan Kompetensi Pedagogi Guru SMPN 3 Semarang Melalui Pelatihan Penggunaan Kecerdasan Buatan (Artificial Intelligence) dalam Pembelajaran di Sekolah - Wahyuni, Sri; Rahmawati, Yusi; Thohiriyah, Thohiriyah; Aryarta, Anggih Restu; Wulandari, Rini Susanti (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The development of information and communication technology, particularly artificial intelligence (AI), holds great potential to enhance the quality of education. SMPN 3 Semarang initiated an AI training program for teachers to strengthen their pedagogical competence. The development of AI in education presents opportunities to enhance teacher competence through technology-based training.This community service activity uses a qualitative descriptive method with a case study approach. Data is collected through observation, interviews, and questionnaires given to training participants. The results of the activity demonstrate that this training offers a comprehensive understanding of the fundamental concepts of AI, its applications in education, and practical skills in utilizing various AI tools and platforms. Additionally, several challenges were identified during the implementation of AI, including limitations in technological infrastructure and teachers' resistance to change.Nevertheless, this training successfully improved teachers' pedagogical competence and made a positive contribution to the quality of learning in schools. This community service activity also made the training in the use of artificial intelligence at SMPN 3 Semarang a model and reference for other schools in improving the quality of learning in this digital era.